Stress, coping styles and personality tendencies of medical students of urban and rural origin - Jolanta Masiak; Małgorzata Kuśpit; Wojciech Surtel; Mirosław J. Jarosz (Annals of Agricultural and Environmental Medicine, 2014)
Introduction. The problem of high levels of stress among medical students is a real problem and its prevalence and mechanisms have not yet been fully explored. It was found that there are only a few publications concerning the influence of urban and rural settings of the medical students in relation to stress, coping styles and personality tendencies. Aim. Analysis of the coping mechanisms and personality types of medical students of rural and urban origin based on the survey of the students of the Medical University in Lublin (MUL), south-east Poland. Material and methods. The study was conducted with a group of 570 medical students from MUL, aged 19–35. Average medical student age: 22. Two questionnaires were used: CISS and SCID II for the evaluation of the coping styles and the personality tendency structures. Results. The place of origin significantly influenced tendencies to the occurrence of specific personality types. The schizotypal, borderline and narcissistic personality tendencies mostly presented in big cities, less in small cities, and the least among students of rural origin. Dependent personality tendencies were significantly more common among females. The coping styles based on avoidance and on looking for the social contacts were significantly more common among females than males. Conclusions. Medical students of urban and rural origin were differentiated in terms of personality structure tendencies, concerning personalities: schizotypal, narcissistic and borderline. The tendencies to the dependent personality were also significantly more common among females than males. Two types of coping styles, based on avoidance and looking for social contacts, were significantly more common among females than males.